Case Study of Drinking Water Distribution Network System PERUMDA Delta Tirta Water Treatment Plant (IPA) Tawangsari Service Zone Taman District and Waru District - Saeril Barikiyah; Abdul Hakim; Sulitiya Nengse (Brawijaya University, 2023)
ABSTRAK Tingkat kehilangan air menurut Menteri Pekerjaan Umum dan Perumahan Rakyat Republik Indonesia No 27/PRT/M/2016 pada batas maksimum yaitu sebesar 20%, akan tetapi pada tingkat kehilangan air PERUMDA Delta Tirta pada zona pelayanan Kecamatan Taman yaitu sebesar 27.48, zona pelayanan Kecamatan Waru I tingkat kehilangan air sebesar 32.28% dan zona pelayanan Kecamatan Waru II tingkat kehilangan air sebesar 20.52%. tujuan pada penelitian ini untuk mengevaluasi tingkat kehilangan air pada zona pelayanan Kecamatan Taman dan zona pelayanan Kecamatan Waru. Metode evaluasi pada jaringan distribusi IPA Tawangsari dengan simulasi software Epanet 2.0 dengan tekanan air dalam pipa dan kecepatan air dalam pipa dibandingka dengan Menteri Pekerjaan Umum dan Perumahan Rakyat Republik Indonesia No 27/PRT/M/2016. Tekanan air dalam pipa pada zona pelayanan Kecamatan Taman yaitu sebesar 55.18 m, kecepatan air dalam pipa sebesar 0.1 m/s dan tekanan air dalam pipa pada zona pelayanan Kecamatan Waru yaitu sebesar 59.57 m, kecepatan air dalam pipa sebesar 1.58 m/s. Optimalisasi sistem jaringan distribusi IPA tawangsari zona pelayanan Kecamatan Taman dan zona pelayanan Kecamatan Waru yaitu dengan pergantian Head pompa. Mengganti head pompa merupakan salah satu solusi untum menghilangkan tekanan yang berlebihan, dan mengurangi kerusakan pada pipa. Kata kunci: distribusi, Sofware Epanet 2.0, tekanan ABSTRACT The water loss rate according to the Minister of Public Works and Public Housing of the Republic of Indonesia No. 27/PRT/M/2016 at the maximum limit is 20%, but at the PERUMDA Delta Tirta water loss rate in the Taman Subistrict service zone is 27.48, the Waru Subdistrict service zone I the water loss rate is 32.28% and the service zone of Waru II District the water loss rate is 20.52%. The purpose of this study was to evaluate the level of water loss in the service zone of the Taman District and the Waru District service zone. The evaluation method for the Tawangsari IPA distribution network is using the Epanet 2.0 software simulation with water pressure in the pipes and water velocity in the pipes compared to the Minister of Public Works and Public Housing of the Republic of Indonesia No. 27/PRT/M/2016. The water pressure in the pipe in the Taman Subdistrict service zone is 55.18 m, the water velocity in the pipe is 0.1 m/s and the water pressure in the pipe in the Waru District service zone is 59.57 m, the water velocity in the pipe is 1.58 m/s. Optimization of the Tawangsari WTP distribution network system in the Taman Subistrict service zone and the Waru Subdistrict service zone, namely by changing the pump head. Replacing the pump head is one of the solutions to eliminate excessive pressure and reduce damage to the pipe. Keywords: distribution, software Epanet 2.0, pressure